Two Cases of Uncommon Complication during Percutaneous Endoscopic Gastrostomy Tube Replacement and Treatment - Lee, Hyun Joo; Choung, Rok Seon; Park, Min Seon; Pyo, Jeung Hui; Kim, Seung Young; Hyun, Jong Jin; Jung, Sung Woo; Koo, Ja Seol; Lee, Sang Woo; Choi, Jai Hyun (The Korean Journal of Gastroenterology, 2014)
We presented two interesting cases of gastrocolocutaneous fistula that occurred after percutaneous endoscopic gastrostomy (PEG) tube placement, and its management. This fistula is a rare complication that occurs after PEG insertion, which is an epithelial connection between mucosa of the stomach, colon, and skin. The management of the fistula is controversial, ranging from conservative to surgical intervention. Endoscopists should be aware of the possibility of gastrocolocutaneous fistula after PEG insertion, and should evaluate the risk factors that may contribute to the development of gastrocolocutaneous fistula before the procedure. We reviewed complications of gastrostomy tube insertion, symptoms of gastrocolocutaneous fistula, and its risk factors. KCI Citation Count: 2